708. Incidence and Relatedness of Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae Infections in Previously Colonized or Infected Patients - Tang, Sarah Si Lin (Open Forum Infect Dis, 2018)
BACKGROUND: In patients with history of carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CPCRE), the need for CPCRE targeted treatment in subsequent sepsis episodes is unclear. We determine the likelihood of CPCRE infection (CI) in patients previously colonized (PC) or infected (PI) with CPCRE and relatedness of both episodes. METHODS: Adult inpatients with CPCRE isolated from any site in June 2012–May 2014 at a tertiary-care hospital were prospectively followed for 2 years to assess for subsequent CI. Bacteria isolates from paired episodes were subjected to Illumina HiSeq2500 and multilocus sequence typing. RESULTS: Six of 25 (24%) PI and 11 of 152 (7%) PC patients had subsequent CI—overall incidence was 9.6%. KP was most commonly implicated. While bacteria species differed in four cases, the carbapenemase type was conserved in all but one. Those with initial bacteremia, intra-abdominal (IA) or lung infection (n = 6) were five times more likely to develop CI. Only 33% of PI vs. 62% of PC patients had subsequent infections of the same clonal group. For PC, KP (OR 9.3) and OXA carbapenemase (OR 12.8) significantly predicted for subsequent CI. In PI, chronic renal failure requiring dialysis (OR 70.2) and KPC enzyme (OR 14) were predisposing factors. In-hospital mortality was observed in six cases. CONCLUSION: Incidence of CI in carriers is low. Patients with IA and respiratory CI in the preceding 93 days are candidates for CPCRE treatment; empiric therapy should be active against the carbapenemase identified in the index episode. DISCLOSURES: All authors No reported disclosures.